Is spinal anaesthesia a suitable technique for ultra-short outpatient procedures? - Fanelli, Andrea; Ghisi, Daniela; Allegri, Massimo (Acta Biomedica Atenei Parmensis, 2013)
Spinal anaesthesia is an easy and reliable technique. Factors limiting its use in the ambulatory setting include delayed ambulation, risk of urinary retention and pain after block regression. On the contrary, general anaesthesia with fast-acting drugs provides a fast recovery that facilitates an early discharge. Although recovery after spinal anaesthesia has been improved by reducing the dose of the commonly used longacting local anaesthetics, discharge times are still prolonged compared with general anaesthesia. 2-Chloroprocaine is an amino-ester local anaesthetic with a very short half-life and a favourable evolution of spinal block for ultra-short outpatient procedures. Moreover, the preservative free 2-chloroprocaine solution showed a very low risk of urinary retention and transient neurological symptoms when compared with bupivacaine and lidocaine. The aim of this article is to evaluate if the neuraxial administration of short-acting local anaesthetics renders spinal anaesthesia a suitable technique for ultra-short surgical procedures.